Comparative analysis of antioxidant activity and structural changes of Gastrodiae Rhizoma polysaccharides between sulfur-fumigation and nonsulfur-fumigation - Dai, Chunyan; Zhao, Dan; Zhang, Wenping; Guo, Lanping; Kang, Chuanzhi; Chen, Zhuowen; Cui, Xiuming; Zhou, Tao; Wang, Chengxiao; Xu, Tingting; Yang, Ye (Frontiers in Nutrition, 2024)
Gastrodiae Rhizoma (referred to Tianma in Chinese), the dried tuber of Gastrodia elata Bl. (Orchidaceae), is utilized as a medicine-food homology product.Sulfur fumigation is commonly employed in the processing of Gastrodiae Rhizoma (GR). Polysaccharides are a crucial active substance produced in GR, yet the impacts of sulfur fumigation on them remain unelucidated. This study aimed to optimize the hot water extraction conditions of polysaccharides from sulfur-fumigated GR (SGCPs) and nonsulfur-fumigated GR (NGCPs). The research explored the effects of sulfur fumigation on the structure and antioxidant activity of GR polysaccharides. The results showed that the optimal extraction conditions for SGCPs and NGCPs were 67°C for 31 min with a liquid-to-material ratio of 15 mL/g and 64°C for 32 min with a liquid-to-material ratio of 17 mL/g, respectively. Compared with NGCPs, SGCPs exhibited significantly reduced DPPH radical, hydroxyl radical, ABTS + radical scavenging activity, and Fe 2+ chelating ability. Moreover, both NGCPs and SGCPs offered significant protective effects against H2O2 -induced oxidative damage in RAW264.7 cells, but the protective effect of SGCPs was significantly lower than that of NGCPs. NMR analyses revealed that the main chain connections of SGCP3 and NGCP3 were both →4)-α-D-Glcp-(1→, and sulfur fumigation increased the number of repeating unit structures →4)-D-Glcp-(1→ in GR polysaccharides. SGCP3 and NGCP3 had the same monosaccharides composition but different molar ratios, with molecular weights of 727650 and 39991 Da, respectively. In general, sulfur fumigation reduced the antioxidant activities of GR polysaccharides by altering their structure and composition.